Effect of everolimus on multifocal micronodular pneumocyte hyperplasia in tuberous sclerosis complex. (2020) - Daccord, Cécile; Nicolas, Aymeric; Demicheli, Rita; Chehade, Hassib; Hottinger, Andreas F.; Beigelman, Catherine; Lazor, Romain
Abstract: Multifocal micronodular pneumocyte hyperplasia (MMPH) is a benign proliferation of alveolar type II cells presenting as multiple pulmonary nodules at chest imaging, which is frequently seen in patients with tuberous sclerosis complex (TSC). We report a case of a woman with TSC and MMPH who received everolimus, a mechanistic target of rapamycin (mTOR) inhibitor, for the treatment of a subependymal giant cell astrocytoma (SEGA). After 3 months of therapy, a remarkable decrease in density of all pulmonary MMPH lesions was observed, without any change in size. This shows that everolimus is active on MMPH similarly to its effects on SEGA, renal angiomyolipomas, and pulmonary lymphangioleiomyomatosis in TSC, and suggests that the dysregulated activation of mTOR which characterizes TSC also plays a role in the pathogenesis of MMPH.